Development of the scanning power supply for 300 keV electron accelerator. Issue 1 (April 2020) - Wah, Leo Kwee; Azhar, M.; Chulan, R.M.; Hashim, S.A.; Mokhtar, M.; Khaidawaton,; Baijan, H.; Sabri, R.M.
Abstract: This paper describes the development and study of the scanning power supply. This locally designed low energy electron accelerator with the former energy of 140 keV will be upgraded to 300 keV. As the setup, scanning power supply is required to excite the scanning coils and deflect the energetic electron beam across a titanium foil window in horizontal and vertical direction respectively. The excitation current of the scanning coils is determined by the energy of the electron beam and the deflected length. Therefore, the scanning power supply must be functioning automatically and continuously to ensure the uniform dose distribution and unavoidable heat issue. As the result, the scanning power supply using the combination of signal generator and power amplifier has been developed and functioning as expected.